Prevalence of Sensitization to Aeroallergens in Greater Beijing Region Children With Respiratory Allergy - Guan, Kai; Zhu, Wenjing; Sha, Li; Liu, Chuanhe; Zhao, Jing; Yin, Jia; Chen, Yuzhi (Frontiers in Pediatrics, 2022)
Objective To evaluate the prevalence and distribution of sensitization to aeroallergens in children with atopic diseases. Methods We conducted skin prick test on 9,527 pediatric patients (aged 0–17 years) with atopic diseases in allergy department of Children's Hospital affiliated with the Capital Institute of Pediatrics. Positive rates of aeroallergens were compared among the different groups. Results Boys (69.5%) had a higher positive rate in SPT results than girls (59.8%; χ2 = 91.7, P < 0.01), and the prevalence of sensitization to aeroallergens increased from 56.1% in the 0–5 year group, to 73.0% in patients above 12 years. Japanese hop (36.2%) and D. farinae (28.1%) were the most common outdoor and indoor aeroallergens, respectively. From low to high age groups, the positive detection rates of D. farinae were 20.3, 30.6, and 33.5%, respectively, followed by D. pteronyssinus (15.7, 24.8, and 30.0%) and cat dander (8.6, 19.8, and 27.9%, respectively), while dog dander and cockroach showed the same trend. The top three positive detection rates of outdoor aeroallergens were Alternaria (30.9%), Japanese Hop (26.7%), and Artemisia (23.7%) in the preschool age group. With regard to patients aged 6 to 11 years, the three most common were Japanese hop (39.2%), Alternaria (36.4%), and Fraxinus pollen (34.4%). Japanese hop (43.8%), Sabina (41.1%), and birch pollen (39.6%) became increasingly common allergens among adolescents. There were more patients with strongly positive reactions to Alternaria in AS (χ2 = 10.2, P < 0.01) and AS with AR groups (χ2 =9.7, P < 0.01) than those in the AR group. Asthmatic patients had significantly higher multiple positive reactions than those with AR (P < 0.01). Asthmatic patients had a much higher prevalence of HDM, animal dander, and Alternaria than those with allergic rhinitis (P < 0.05). Conclusion The prevalence of sensitization to aeroallergens increased with age in children with atopic diseases in Greater Beijing Region. Alternaria was the predominant allergen before 5 years of age, and tree pollen had delayed sensitization in adolescents. Sensitization to perennial allergens such as HDM, cats, and Alternaria was more strongly associated with asthma risk. Sensitization to more than one allergen significantly affected asthmatic patients.